2011
DOI: 10.1007/s00432-011-1006-0
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between BARD1 Cys557Ser variant and breast cancer risk: a meta-analysis of 11,870 cases and 7,687 controls

Abstract: This meta-analysis strongly suggests that BARD1 Cys557Ser mutation is not associated with increased breast cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Moreover, some non-synonymous polymorphisms (e.g., cys557Ser, Arg378Ser, Val507Met, and Pro24Ser) in the BARD1 gene have been also frequently investigated for their association with cancer susceptibility, and studies mainly involved breast cancer (Morris et al, 2006, Onay et al, 2006, Stacey et al, 2006, Vahteristo et al, 2006, Guenard et al, 2009, Ding et al, 2011, Sun et al, 2012), neuroblastoma (Capasso et al, 2009, Capasso et al, 2013), and cervical cancer (Zhou et al, 2009). Nonetheless, the associations between these BARD1 SNPs and cancer susceptibility have been often paradoxical.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, some non-synonymous polymorphisms (e.g., cys557Ser, Arg378Ser, Val507Met, and Pro24Ser) in the BARD1 gene have been also frequently investigated for their association with cancer susceptibility, and studies mainly involved breast cancer (Morris et al, 2006, Onay et al, 2006, Stacey et al, 2006, Vahteristo et al, 2006, Guenard et al, 2009, Ding et al, 2011, Sun et al, 2012), neuroblastoma (Capasso et al, 2009, Capasso et al, 2013), and cervical cancer (Zhou et al, 2009). Nonetheless, the associations between these BARD1 SNPs and cancer susceptibility have been often paradoxical.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is critical that all association studies consider external validity issues and candidly state the populations to which the results can be applied. Several meta-analyses were undertaken to reevaluate such associations (Ding et al, 2011, Liu et al, 2015). Ding et al reported a lack of association between BARD1 Cys557Ser polymorphism and breast cancer risk in a pooled analysis comprising 11,870 cases and 7687 controls in 2011 (Ding et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of germline BARD1 mutations in the development of BC is also unclear . Germline BARD1 mutations in those with suspected hereditary BC have been identified but an associated increased relative risk for BC has not been demonstrated .…”
Section: Discussionmentioning
confidence: 99%
“…However, p.C557S is functional in HDR [Laufer et al., ] and in subsequent studies has been shown to have similar allele frequencies in individuals from breast cancer families and controls [Vahteristo et al., ; Ratajska et al., ]. Furthermore, case‐control studies in sporadic breast cancer studies showed no evidence of increased risk [Ding et al., ]. Thus, data suggests that this variant is likely neutral/benign.…”
Section: Discussionmentioning
confidence: 99%